War and Journalism : The Presentation of Conflict and Provision of Actuality - Jacob, Frank, (Schöningh and Fink Early Modern and Modern History E-Books Online, Collection 2025., 2024)
It were journalists that made war accessible for private households since the 19th century. Detailed reports and images brought the front to the living room and people around the world could follow military action on a daily basis. The people who reported about wars therefore shaped the perceptions of the respective conflicts and could even turn into political agents. This volume presents several case studies demonstrating how war and journalism were tied together on multiple levels. The contributions reflect questions related to agency, description, perception and politics alike. The authors explore which role journalists actually played in times of war and conflict and how their work fits into the overall history of violence since the 19th century.